Effects of the buried straw layer on soil water and nitrogen distribution under different irrigation limits - Rasool, Ghulam; Zhang, Shuxuan; Wu, Feng; Guo, Xiangping (International Journal of Agricultural and Biological Engineering, 2022)
At present, water and fertilizer use efficiency is low in many cultivation areas in southern China. Studies show that the buried straw layer can effectively conserve water and fertilizer. To investigate the optimal irrigation upper limit above the straw barrier and its effect on soil moisture and nitrogen distribution, an indoor soil column experiment was conducted. Six treatments were designed consisting of two levels of straw layer i.e., (with and without buried straw layer at 25 cm depth), and three irrigation water upper limits i.e., (saturated moisture content (s), field water holding capacity (f), and 80% of field water holding capacity (0.8f) as the upper limit of irrigation). The result revealed that the buried straw layer can inhibit water infiltration and significantly increase the water storage capacity and water storage efficiency of 0-25 cm soil depth. Under the condition of no evaporation, when the upper limit of irrigation water does not exceed the field water holding capacity, the storage efficiency of 0-25 cm soil water reaches 89%-91% after 6 d. Moreover, a buried straw layer can inhibit the deep percolation of nitrate nitrogen and increase the amount of nitrate-nitrogen in 0-25 cm soil. The 80% field water holding capacity irrigation upper limit combined with straw interlayer treatment had a higher nitrate-nitrogen content in the 0-25 cm soil layer than other treatments. Therefore, 80% of field water holding capacity as the upper limit of irrigation combined with buried straw layer is the optimal strategy to conserve soil water and nitrogen in the upper soil profile.Keywords: distribution of water and nitrogen, irrigation water levels, infiltration, water storage efficiencyDOI: 10.25165/j.ijabe.20221505.6160Citation: Rasool G, Zhang S X, Wu F, Guo X P. Effects of the buried straw layer on soil water and nitrogen distribution under different irrigation limits. Int J Agric & Biol Eng, 2022; 15(5): 141–145.